CARDIOLOGY AND GENETICS (Multidisciplinary Journal of Science and Technology, 2024)
Hereditary cardiovascular diseases make a significant contribution to the structure of cardiovascular pathology. The article is devoted to a review of materials on genetically determined cardiac diseases, which were discussed at the First International Congress “Genetics and the Heart”. The most current data on hypertrophic and dilated cardiomyopathies and hereditary problems of arrhythmogenesis are presented. The main participants of the congress are listed